Rio 2.0: revising the Rio scale for SETI detections. Issue 4 (24th August 2019) - Forgan, Duncan; Wright, Jason; Tarter, Jill; Korpela, Eric; Siemion, Andrew; Almár, Iván; Piotelat, Elisabeth
Abstract: The Rio scale is a tool for communicating the significance of a signal to the general public. It assigns scores to signals detected in searches for extraterrestrial intelligence (SETI), which characterizes both the consequences of a signal and the probability the signal is truly from ETI, in an easily digestible format for laypeople to interpret. In the 17 years since its construction, the number of groups actively conducting searches for evidence of intelligent life beyond the Earth has increased significantly, and theoretical work has established a new suite of observables that are capable of revealing the presence of ETI in a range of astronomical observations. In this paper, we revise the Rio scale, with the aim of (i) achieving consensus across academic disciplines on a scheme for classifying signals potentially indicating the existence of advanced extraterrestrial life, (ii) supplying a pedagogical tool to help inform the public about the process scientists go through to develop an understanding of a signal and (iii) providing a means of calibrating the expectations of the world at large when signals are discussed in the media. We also present (and encourage the SETI community to adopt) a single set of consistent terminology for discussing signals.